2006
DOI: 10.1016/j.febslet.2006.03.041
|View full text |Cite
|
Sign up to set email alerts
|

DU‐145 and PC‐3 human prostate cancer cell lines express androgen receptor: Implications for the androgen receptor functions and regulation

Abstract: The majority of human prostate cancer cell lines, including the two "classical" cell lines DU-145 and PC-3, are reported to be androgen receptor (AR)-negative. However, other studies have provided evidence that the DU-145 and PC-3 cell lines express AR mRNA. These contradictory observations prompted us to investigate whether DU-145 and PC-3 cell lines express the androgen receptor. Using antipeptide antibodies directed against three distinct regions of the human AR protein and an improved method to detect AR p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
153
2
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(170 citation statements)
references
References 32 publications
11
153
2
3
Order By: Relevance
“…47 PC3 cells were chosen because they are PSA negative and although they are considered AR-negative they do express low AR mRNA and protein levels 48 in addition to retaining co-regulators necessary for AR activity in prostate tumor progression. 49 Therefore, changes in PSA promoter activity would be accurately reflected after incubation with urolithins and/or DHT in these reporter assays.…”
Section: Urolithins a And B Inhibit The Psa Promoter Activitymentioning
confidence: 99%
“…47 PC3 cells were chosen because they are PSA negative and although they are considered AR-negative they do express low AR mRNA and protein levels 48 in addition to retaining co-regulators necessary for AR activity in prostate tumor progression. 49 Therefore, changes in PSA promoter activity would be accurately reflected after incubation with urolithins and/or DHT in these reporter assays.…”
Section: Urolithins a And B Inhibit The Psa Promoter Activitymentioning
confidence: 99%
“…Consequently, we considered the possibility that either our immunoblotting conditions to detect relatively low levels of IFI16 protein in prostate cancer cell lines were not optimum or the expression of IFI16 gene is silenced in prostate cancer cell lines. Therefore, we chose to use our recently optimized (19) immunoblotting conditions to detect the expression of IFI16 protein. Using the optimized conditions for immunoblotting, we were able to detect basal low levels of IFI16 protein in both LNCaP and DU-145 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The lysis buffer was supplemented with complete mini EDTA-free protease inhibitor cocktail (Roche Diagnostic Corporation, Indianapolis, IN). Cell lysates containing approximately equal amounts of protein were subjected to immunoblotting using the optimized conditions to detect low levels of IFI16 protein as described previously (19). In brief, proteins were transferred to Immobilon-P (pore size, 0.45 Am; Millipore, Bedford, MA) transfer membranes using the transfer buffer with 0.01% SDS (w/v).…”
Section: Immunoblotting and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The results showing altered OPG protein following 5a-DHT treatment in PC-3 cells were surprising, as PC-3 is considered to be androgen-independent. However, recent studies examining expression of AR mRNA and Androgen decreases OPG protein in CaP cells K Vandyke et al protein in PC-3 cells have produced conflicting results, 22,[24][25][26] although none of these investigations showed transcriptional activation of androgen-responsive genes by endogenous AR protein or any effect on proliferation of the PC-3 cells tested. 22,27,28 The PC-3 cells used in our study were found to express detectable levels of AR mRNA but did not produce detectable levels of AR protein as assessed by Western blot analysis ( Figure 5) and exhibited no growth response to androgens (data not shown), suggesting either that the effects of androgen in this cell line were mediated via AR-independent me- Androgen decreases OPG protein in CaP cells K Vandyke et al chanisms or that levels of AR protein were too low to elicit activation of androgen-responsive genes.…”
Section: Discussionmentioning
confidence: 99%